Alterations in blood pressure dependent activation of leg muscles during standing following bed rest mimic those observed with ageing - Tremblay, Malcom; Xu, Da; Verma, Ajay K.; Goswami, Nandu; Blaber, Andrew P. (Frontiers in Physiology, 2025)
IntroductionBaroreflex-mediated activation of lower leg muscles (i.e., muscle-pump baroreflex) has been suggested to play a significant role in blood pressure regulation during standing. Compromised muscle-pump baroreflex because of ageing or prolonged inactivity could contribute to orthostatic hypotension. Understanding the contribution of individual lower leg muscles to blood pressure regulation could lead to the development of muscle-specific strategies to prevent orthostatic hypotension associated with muscle-pump baroreflex dysfunctions.MethodsIn this study, individual muscle (tibialis anterior (TA), lateral soleus (SOL), medial gastrocnemius (MG), and lateral gastrocnemius (LG)) responses to blood pressure changes upon a supine-to-stand orthostatic challenge were examined in young adult male participants (35 ± 2 years) before and after 60 days of 6° head-down tilt bed rest (HDBR). By analyzing the interactions between systolic blood pressure (SBP) and heartbeat-by-heartbeat electromyogram impulse (EMGimp) during standing, the interactions between SBP and EMGimp including muscle-pump baroreflex were characterized by fraction time active (FTA) and response gain from wavelet transform coherence analysis and the causality values using convergent cross mapping method for individual leg muscles. Since inactivity and ageing are common causes of orthostatic intolerance, the HDBR results were compared with those from young and older individuals in a previously published study to investigate the similarities in their effects on muscle-pump baroreflex.ResultsDuring standing, FTA reduced for all muscles except MG following HDBR and was lower in older compared to younger participants. Muscle-pump baroreflex causality (SBP→EMGimp) reduced for all muscles following HDBR and was lower for LG and SOL muscles in older compared to younger adults. The mechanical muscle-pump causality (SBP→EMGimp) was not affected by HDBR or by age. Increased TA muscle-pump baroreflex gain post-HDBR may point to a compensatory mechanism for decreased active control.ConclusionsOur results showed striking similarities in the alteration of muscle-pump baroreflex induced via ageing and HDBR, suggesting strong commonalities between ageing and long-term inactivity in terms of the adverse effects on baroreflex mediated control of lower leg muscle activities in response to orthostatic challenge.